1997
DOI: 10.1111/j.1467-9280.1997.tb00450.x
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Pitch as a Perceptual Analogue to Odor Quality

Abstract: A bstract-Experitnuits in cross-modal niatcliing siiggest that stitells can be arranged by odor qiiality along the color diniensions of liiie arid liglitness. Here we report that subjects readily aa'jilrst the Ioiidness-eqiialized pitcli of mi aiiditory tone to niatclt a stiniiiliis odor. Tlie resiilts olloiv odors to be arranged in seqiience by their pitclteqiiiralerits. Tlie torte nmtches appear to be based 011 perceptual featiires of olfaction other tlian stiltiiiliis intensitj or pleasarimess. Tlie resiilr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
107
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(126 citation statements)
references
References 13 publications
5
107
2
3
Order By: Relevance
“…There could be many possible reasons for this; following are a few of the more likely explanations: (i) that there exists corresponding dimensions between sensory modalities, although not between auditory frequency/grey pictures and olfaction, at least not for whiskey or n-butanol. This would contradict an earlier study by Belkin et al (1997), who found that people assign certain frequencies to different odors. Although, the designs of the experiments differ, and so does the presented olfactory stimuli; thus, no conclusive inferences can be made.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…There could be many possible reasons for this; following are a few of the more likely explanations: (i) that there exists corresponding dimensions between sensory modalities, although not between auditory frequency/grey pictures and olfaction, at least not for whiskey or n-butanol. This would contradict an earlier study by Belkin et al (1997), who found that people assign certain frequencies to different odors. Although, the designs of the experiments differ, and so does the presented olfactory stimuli; thus, no conclusive inferences can be made.…”
Section: Discussioncontrasting
confidence: 55%
“…If there were actual correspondences between, say, sound frequency and grayscale, the participants may have used the same strategy for the remaining matching's, because of a belief that this was what was expected from them. One alternative procedure could have been the method used by Belkin et al (1997), i.e., letting the subjects choose what frequency actually corresponded to each odor. Those frequencies could later on be used in the experimental design presented here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…sweet) with sounds which are liked more. However, Crisinel and Spence (2012) by testing those who liked or disliked dark chocolate showed that pleasantness matching cannot fully explain the mapping between sweet (bitter) taste and high (low) pitch (see also Belkin, Martin, Kemp, & Gilbert, 1997). In the current study, hedonic relationships appeared to play an important role for the observed sound-taste mappings.…”
Section: Theoretical Implicationsmentioning
confidence: 99%